Antibody responses and SARS-CoV-2 infection after BNT162b2 mRNA booster vaccination among healthcare workers in Japan. Issue 11 (November 2022) - Igari, Hidetoshi; Asano, Haruna; Murata, Shota; Yoshida, Toshihiko; Kawasaki, Kenji; Kageyama, Takahiro; Ikeda, Key; Koshikawa, Hiromi; Okuda, Yoshio; Urushihara, Misao; Chiba, Hitoshi; Yahaba, Misuzu; et al.
Abstract: Introduction: Vaccine effectiveness against SARS-CoV-2 infections decreases due to waning immunity, and booster vaccination was therefore introduced. We estimated the anti-spike antibody (AS-ab) recovery by booster vaccination and analyzed the risk factors for SARS-CoV-2 infections. Methods: The subjects were health care workers (HCWs) in a Chiba University Hospital vaccination cohort. They had received two doses of vaccine (BNT162b2) and a booster vaccine (BNT162b2). We retrospectively analyzed AS-ab titers and watched out for SARS-CoV-2 infection for 90 days following booster vaccination. Results: AS-ab titer eight months after two-dose vaccinations had decreased to as low as 587 U/mL (median, IQR (interquartile range) 360–896). AS-ab titer had then increased to 22471 U/mL (15761–32622) three weeks after booster vaccination. There were no significant differences among age groups. A total of 1708 HCWs were analyzed for SARS-CoV-2 infection, and 48 of them proved positive. SARS-CoV-2 infections in the booster-vaccinated and non-booster groups were 1.8% and 4.0%, respectively, and were not significant. However, when restricted to those 20–29 years old, SARS-CoV-2 infections in the booster-vaccinated and non-booster groups were 2.9% and 13.6%, respectively (p = 0.04). After multivariate logistic regression, COVID-19 wards (adjusted odds ratio (aOR):2.9, 95% confidence interval (CI) 1.5–5.6) and those aged 20–49 years (aOR:9.7, 95%CI 1.3–71.2) were risk factors for SARS-CoV-2 infection. Conclusions: Booster vaccination induced the recovery of AS-ab titers. Risk factors for SARS-CoV-2 infection were HCWs of COVID-19 wards and those aged 20–49 years. Increased vaccination coverage, together with implementing infection control, remains the primary means of preventing HCWs from SARS-CoV-2 infection.